Photomechanical Energy Conversion of Photoresponsive Fibers Exhibiting Bending Behavior. (13th September 2012) - Nakata, Kazuya; Ishikawa, Yosuke; Sakai, Munetoshi; Liu, Baoshun; Ochiai, Tsuyoshi; Sakai, Hideki; Murakami, Taketoshi; Abe, Masahiko; Fujishima, Akira
Abstract : Photoresponsive fibers based on poly(acrylamide) (PAA) with methylene blue (MB) dye were prepared. All semicircular fibers show bending towards the direction of the flat surface of the fiber when illuminated. The fibers recover their initial shape when the illumination stops. The fiber is heated upon illumination and cooled to room temperature once the illumination is stopped. The fiber also is sensitive to humidity, showing bending behavior towards the direction of the flat surface of the fiber upon changing the humidity. The mechanical energy of the PAA/MB fiber is approximately 0.6 mN for the bending direction when it is illuminated. A possible mechanism for the bending behavior is as follow: (1) the fiber is heated upon illumination because of the photothermal effect, (2) the fiber loses water molecules, (3) the fiber shrinks; bending towards the direction of the flat surface of the fiber occurs because of a difference in the shrinkage for the flat surface and the other side of the fiber. Finally, we demonstrated that a PP ball (1.5 mg) can be moved by the mechanical energy produced by the changing shape of the fiber upon illumination.